Dieta vegetariana estrita e suas implicações no biomarcador inflamatório proteína c-reativa e no desempenho após um protocolo de treino de força - Bruno Sena Piconi (2023)
The study has an analytical cross-sectional design and aimed to investigate the impact of a strict vegetarian diet on the inflammatory biomarker C-reactive Protein (CRP) and performance after a strength training protocol (STP). The sample consisted of 18 volunteers in total, with 8 men and 1 woman for each of the two groups: strict vegetarian (VEG) (25,14 ± 2,40 years, 69,56 ± 9,73 kg) for at least 6 consecutive months or an omnivorous diet (ONI) (22,68 ± 3,40 years, 72,16 ± 10,94 kg). The volunteers underwent a training session with 10 total sets (5 sets of Smith Machine Squats and 5 sets of 45° Leg Press) performed to muscular failure. For CRP assessment, blood samples were collected to measure CRP. Performance was measured from the countermovement jump and recorded the jump height (JH), the maximum isometric contraction (MIC), both performed on a force platform, and by the maximum repetitions test (RM) performed at 10RMs intensity (%10RM). Two-way ANOVA (diet x time) with repeated measures identified that CRP did not differ between the groups (p=0,681), but was significantly higher at 24h compared to other times (p<0,01) and higher at 48h compared to the pre-training moment (p=0,042). JH did not differ between groups (p=0,911) and evaluated moments (p= 0,051). The MIC did not differ between groups (p=0,643), but was significantly lower at 48h in ONI compared to the pretraining moment in ONI (Ptukey= 0,012). For %10RM, there were no differences between groups (p=0,60) and moments (p=0,065). Regarding food intake, VEG had a lower average protein intake than ONI (VEG: 16,71 ± 6,50 vs ONI: 25,03 ± 6,94; p=0.025) and a higher average carbohydrate intake (VEG: 61,28 ± 8,97 vs ONI: 51,65 ± 5,96; p=0.024). Strict vegetarians did not show differences in CRP responses and performance after an STP compared to omnivores.